2020
DOI: 10.1111/pai.13411
|View full text |Cite
|
Sign up to set email alerts
|

Maternal antibiotic exposure during pregnancy and the risk of allergic diseases in childhood: A meta‐analysis

Abstract: Background: Increasing studies suggest that antibiotic exposure during pregnancy may increase the risk of childhood allergic diseases; however, controversy still exists. Thus, we conducted this meta-analysis to evaluate the association between antibiotic use during pregnancy and childhood asthma/wheeze, eczema/atopic dermatitis, and food allergy. Methods: CENTRAL, EMBASE, and PubMed were searched for studies up to July 20, 2020. Cohort studies and case-control studies that estimated the association of antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 60 publications
(233 reference statements)
4
35
0
Order By: Relevance
“…We found that prenatal exposure to antibiotics was associated with an increased risk for IBD development. Antibiotic exposure could influence microbial colonization in utero, [131] the offspring of antibiotic-exposed mothers has been shown to display reduced abundance of Bifidobacterium and Lactobacillus, [132] and positive associations have been reported with asthma/wheezing and eczema/ atopic dermatitis, [133] pointing to biological plausibility in our findings. Our analysis for postnatal antibiotic exposure showed a trend toward increased risk of IBD.…”
Section: Discussionsupporting
confidence: 60%
“…We found that prenatal exposure to antibiotics was associated with an increased risk for IBD development. Antibiotic exposure could influence microbial colonization in utero, [131] the offspring of antibiotic-exposed mothers has been shown to display reduced abundance of Bifidobacterium and Lactobacillus, [132] and positive associations have been reported with asthma/wheezing and eczema/ atopic dermatitis, [133] pointing to biological plausibility in our findings. Our analysis for postnatal antibiotic exposure showed a trend toward increased risk of IBD.…”
Section: Discussionsupporting
confidence: 60%
“…The risk factors for the development of AD in childhood include a family history of allergic diseases, living in an urban area, exposure to antibiotics, and a high‐sugar diet 5 . However, maternal factors (eg, smoking exposure, breastfeeding, and maternal antibiotic consumption 6 ) that affect the risk of AD in children have received increasing attention 7,8 …”
Section: Introductionmentioning
confidence: 99%
“…Animal models have supported this concept by showcasing the positive correlation between antibiotic and antifungal treatment and enhanced asthma severity ( 203 , 252 254 ). Moreover, several studies report an association between prenatal and early life antibiotic exposure in humans and increased risk of asthma development ( 251 , 255 260 ). Additionally, antibiotic treatment causes longer hospitalization stays and higher costs ( 261 ), and have not proven to be beneficial in alleviating asthma exacerbations in adults ( 262 ).…”
Section: Current Treatment Strategies For Asthma Symptom Prevention A...mentioning
confidence: 99%